Solution Optimal Transportation Problems Using the Sirisha Viola Modification Method Python assisted programming - Fahrudin Muhtarulloh; Aisyah Maulidina; Arief Fatchul Huda (JINAV: Journal of Information and Visualization, 2023)
One of the problems that exist in operations research is the problem of transportation. This study proposes the completion of the optimal solution in the transportation problem using the Modified Method of the Sirisha Viola method. The method proposed hereinafter is called the Sirisha Viola Modified Method . The algorithm in this method is the same as in the Sirisha Viola method but differs in the allocation step, where the allocation is made to the minimum demand first, then compared with the corresponding supply value. The data used in this study consisted of secondary data and simulated data (random data). The results of numerical calculations or using the help of the Python program for secondary data obtained an optimal solution of 12,100 cost units. Whereas for random data consisting of 4 0 balanced data and 40 unbalanced data with sizes 10 x 10, 13 x 17, 25 x 27, and 50 x 50 the optimal solution results are obtained. It is concluded that the Sirisha Viol a Modification Method in solving transportation problems can produce optimal solutions directly without the need to determine the initial feasible solution.